Ca lâm sàng: Bệnh Melioidosis (Whitmore) - Hương, Hoàng Thị Lan; Vĩnh, Trần Duy; Loan, Phan Thị Thanh; Nguyệt, Hoàng Thị Ánh; Trinh, Phan Thị Thùy (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
.